Synthesis, Spectral, Magnetic and Thermal Studies of the Complexes of CoII and NiII With Some Bidentate and Tridentate Hydrazone Ligands - Chetan K. Modi; Ashwin S. Patel; Bharat T. Thaker (E-Journal of Chemistry)
The reaction of Co(NO3)2.6H2O and Ni(NO3)2.6H2O with hydrazones derived from 1-phenyl-3-methyl-4-acyl-5-pyrazolone (where acyl = acetyl, propionyl, butyryl and benzoyl) with 2-picolinic acid hydrazide have been studied and characterized on the basis of elemental analysis, magnetic moments, molar conductivity measurements, IR and electronic spectral studies and thermogravimetric analysis. Various ligand field parameters have been calculated. Electronic spectral data and the magnetic moment values suggest an octahedral structure for all cobalt(II) and nickel(II) complexes.